Evaluasi Keandalan Fisik Bangunan Gedung (Studi Kasus di Wilayah Kabupaten Sleman) - Mandiyo Priyo , Ibnu Herlambang Sujatmiko (Universitas Muhammadiyah Yogyakarta, 2011)
Since 2002 has made rules about Bangunan Gedung (UUBG) that is UU no. 28 and in 2005 also made rules of realization that is Rule of Government No. 36 where the contain is a building should managed administration and also technical. This research is to find outlevel of reliability of buildings from architect aspects there are structure, utility, and fire protection, ability of access, and also building sand and environment in Sleman regency. Survey method (measuring, counting and filling in survey forms) was implemented to collect the primary data from the samples, and the secondary data being used were IMBs (building construction licenses), PBB (land and building tax) slips, etc. The data were analysed using descriptive statistic and scoring depends on the book entitled Panduan Teknis Tata Cara Pemeriksaan Keandalan Bangunan Gedung, 1998, Dept. PU, and Peraturan Permen PU No.29/PRT/M/2007, Permen PU No.26/PRT/M/2008. The criteria being used to determine the building reliability were Reliable for score of 95-100, Less Reliable for score of 75-95, Not Reliable for score of 75.The result shows that the building reliability of the Stikes being 96.51, the PMI being 94.20, the BBLK being 93.10, the RSUD being 93.36, and the Rukan being 87.68.